PENGARUH TIPE TANAH TERHADAP KOMUNITAS RAYAP TANAH - Ginuk Sumarni; Agus lsmanto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Beside temperature and humidity, soil type is an important factor that effects termite population size. From three types of soil selected for the study (association of dark grey alluvial and greyish brown, grey regosol and association of low peat glei and grey alluvial), three termite species, namely Microtermes insperatus Kemner, M. incertoides Holmgren and Macrotermes gilvus (Hagen) were observed. These three species of termite inhabited the low peat glei and grey alluvial soil. In the association of dark grey alluvial and greyish brown soil, only M. gilvus was observed. This same species of termite was also spotted the grey regosol soil.The number of termite individuals found in the three types of soil were obviously different. The greatest number were observed in the association of low peat glei and grey alluvial soil.